2004
DOI: 10.1002/jcp.20230
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma cells deficient in DNA‐dependent protein kinase are resistant to cell death

Abstract: DNA-dependent protein kinase (DNA-PK), a nuclear serine/threonine kinase, is responsible for the DNA double-strand break repair. Cells lacking or with dysfunctional DNA-PK are often associated with mis-repair, chromosome aberrations, and complex exchanges, all of which are known to contribute to the development of human cancers including glioblastoma. Two human glioblastoma cell lines were used in the experiment, M059J cells lacking the catalytic subunit of DNA-PK, and their isogenic but DNA-PK proficient coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
6
9
0
Order By: Relevance
“…The increased cell death shown in DNA-PKcs proficient glioblastoma cells supports the view that TQ targets DNA-PKcs proficient glioblastoma cells and that DNA-PKcs activation may play a role in apoptosis. This finding corroborates an earlier study, which showed a greater resistance of DNA-PKcs deficient glioblastoma cells to cell death as compared to DNA-PKcs proficient glioblastoma [29].…”
Section: Discussionsupporting
confidence: 92%
“…The increased cell death shown in DNA-PKcs proficient glioblastoma cells supports the view that TQ targets DNA-PKcs proficient glioblastoma cells and that DNA-PKcs activation may play a role in apoptosis. This finding corroborates an earlier study, which showed a greater resistance of DNA-PKcs deficient glioblastoma cells to cell death as compared to DNA-PKcs proficient glioblastoma [29].…”
Section: Discussionsupporting
confidence: 92%
“…A prior investigation has reported decreased Bax levels in the M059J glioblastoma cell line, lacking DNA-PKcs expression, as compared with its isogenic M059K control [12]. We have not observed differences in Bax levels, by Western blot analysis, in either murine cortices or in cultured cortical neurons, regardless of DNA-PKcs status, consistent with others [28].…”
Section: Discussionsupporting
confidence: 91%
“…Our functional proteomic data suggest candidates like AKT1 and 2, MAPK14, and BRAF for future investigation (Figure 3C). Disrupting such kinases could reveal the functional contribution that they (and their cognate substrates) make to apoptosis, as has been shown previously for DNA-PK (Bharti et al, 1998; Chakravarthy et al, 1999; Chen et al, 2005a, b; Wang et al, 2000). Finally, there are other potential forms of crosstalk between phosphorylation and proteolytic pathways that may have eluded detection in our study.…”
Section: Discussionmentioning
confidence: 69%